1981
DOI: 10.2166/nh.1981.0022
|View full text |Cite
|
Sign up to set email alerts
|

Snow Surface Measurements from Digital Landsat MSS Data

Abstract: The snow cover is an important parameter for water run-off prediction in high mountain areas. At present its seasonal changes can be monitored regularly by satellite. The paper presents a new method for a more accurate classification of snow from multispectral Landsat data with the aid of a digital terrain model (DTM). A reflectance map derived from the DTM was used to register the Landsat data onto the map applying the cross-correlation function. The DTM makes the independent evaluation of snow possible with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 2 publications
0
10
0
Order By: Relevance
“…For example, McGuire et al (2005) and Andreadis and Lettenmaier (2006) reported only being able to use SCA images for days where cloud obscuration was less than 20 % of the grid cell, while Rodell and Houser (2004) used 6 % as the threshold for minimum visibility. Consequently, several investigations into techniques for removing cloud cover from SCA images have been reported (e.g., Lichtenegger et al, 1981;Seidel et al, 1983;Molotch et al, 2004;Parajka and Blöschl, 2008;Gafurov and Bárdossy, 2009).…”
Section: The Problem Of Cloud Obscurationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, McGuire et al (2005) and Andreadis and Lettenmaier (2006) reported only being able to use SCA images for days where cloud obscuration was less than 20 % of the grid cell, while Rodell and Houser (2004) used 6 % as the threshold for minimum visibility. Consequently, several investigations into techniques for removing cloud cover from SCA images have been reported (e.g., Lichtenegger et al, 1981;Seidel et al, 1983;Molotch et al, 2004;Parajka and Blöschl, 2008;Gafurov and Bárdossy, 2009).…”
Section: The Problem Of Cloud Obscurationmentioning
confidence: 99%
“…Lichtenegger et al (1981) and Seidel et al (1983) used elevation, slope, exposure, and brightness information from a digital terrain model (DTM) to extrapolate snow cover from cloud-free to cloud-covered areas in digital Landsat multispectral scanner data, assuming that for each elevation zone, the regions with equivalent exposure and slope angle carry the same amount of snow. Molotch et al (2004) filtered NOHRSC SCA maps (based on AVHRR/GOES data) using gridded positive accumulated degree days (ADD) and AVHRR-derived binary SCA to obtain a threshold for defining snow cover in the Salt and Verde rivers in Arizona.…”
Section: The Problem Of Cloud Obscurationmentioning
confidence: 99%
“…Even data with a resolution of 5 km used in conjunction with NOAA-AVHRR would be very useful. Some methods to extrapolate visible snow mapping from cloud-free to cloud-covered areas have also been developed (Lichtenegger et al, 1981 ;Baumgartner et al, 1986) and can be used in partly cloudy situations. Such methods use digital topographical data and assume that pixels with equal elevation, aspect and slope have the same relative snow coverage over all the basin.…”
Section: Challenging Problem Areasmentioning
confidence: 99%
“…When a basin is partially snow covered, a method has been developed to estimate the snow cover in the cloud-obscured parts of the basin (Lichtenegger et al, 1981;Baumgartner et al, 1986). The method uses digital topographic data and assumes that pixels with equal elevation, aspect and slope have the same relative snow coverage over all the basin.…”
Section: Visible Band Monitoringmentioning
confidence: 99%